The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0127971
|View full text |Cite
|
Sign up to set email alerts
|

Blast-Associated Shock Waves Result in Increased Brain Vascular Leakage and Elevated ROS Levels in a Rat Model of Traumatic Brain Injury

Abstract: Blast-associated shock wave-induced traumatic brain injury (bTBI) remains a persistent risk for armed forces worldwide, yet its detailed pathophysiology remains to be fully investigated. In this study, we have designed and characterized a laboratory-scale shock tube to develop a rodent model of bTBI. Our blast tube, driven by a mixture of oxygen and acetylene, effectively generates blast overpressures of 20–130 psi, with pressure-time profiles similar to those of free-field blast waves. We tested our shock tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 63 publications
4
52
0
Order By: Relevance
“…In other rat models, blast-induced BBB leakage appeared preferentially at higher blast pressures (>110-kPa), as it was shown that extensive leakage occurred in all brain regions but preferentially in the thalamus, striatum, hippocampus, and occipital cortex [25,29]. However, limited leakage, mainly through the chorionic plexus, was observed after exposure to 72-kPa blasts [25,29,49]. Kawoos et al [29] also showed that there is a qualitative relationship between BBB leakage and increased intracerebral pressure (ICP), through which the ICP levels and sustainability depend also on blast intensity and the number of blast exposures.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In other rat models, blast-induced BBB leakage appeared preferentially at higher blast pressures (>110-kPa), as it was shown that extensive leakage occurred in all brain regions but preferentially in the thalamus, striatum, hippocampus, and occipital cortex [25,29]. However, limited leakage, mainly through the chorionic plexus, was observed after exposure to 72-kPa blasts [25,29,49]. Kawoos et al [29] also showed that there is a qualitative relationship between BBB leakage and increased intracerebral pressure (ICP), through which the ICP levels and sustainability depend also on blast intensity and the number of blast exposures.…”
Section: Discussionmentioning
confidence: 92%
“…Acutely, after 72 h, animals exposed to 74.5-kPa blasts present pathological alterations that mainly included blood leakage from the choroid plexus into the lateral ventricles, focal non-hemorrhagic tissue tears, and vascular alterations [17,49]. In other rat models, blast-induced BBB leakage appeared preferentially at higher blast pressures (>110-kPa), as it was shown that extensive leakage occurred in all brain regions but preferentially in the thalamus, striatum, hippocampus, and occipital cortex [25,29]. However, limited leakage, mainly through the chorionic plexus, was observed after exposure to 72-kPa blasts [25,29,49].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations